2007
DOI: 10.1590/s0066-782x2007000400013
|View full text |Cite
|
Sign up to set email alerts
|

Um estudo sobre hipertensão arterial sistêmica na cidade de Campo Grande, MS

Abstract: SummaryObjectives: To detect the actual prevalence of systemic hypertension in the city of Campo Grande, State of Mato Grosso do Sul, Brazil, and frequent risk factors.Methods: Cross-sectional study with a randomized sample of the adult population of the city of Campo Grande, MS, in a total of 892 individuals. A questionnaire on age, gender, level of education, smoking, alcohol consumption, and aspects of the treatment was applied. Anthropometric data (weight and height) were collected. According to the WHO, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
24

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 2 publications
3
30
0
24
Order By: Relevance
“…In this article, a significant increase was noted in the prevalence of hypertension among individuals who were overweight, as had already been reported in other studies 5,[19][20][21] .…”
Section: Discussionsupporting
confidence: 86%
“…In this article, a significant increase was noted in the prevalence of hypertension among individuals who were overweight, as had already been reported in other studies 5,[19][20][21] .…”
Section: Discussionsupporting
confidence: 86%
“…Estima-se que cerca de um terço dos hipertensos nunca teve o diagnóstico clínico da doença feito por um profissional de saúde 7 , e muitas vezes tomam ciência da doença apenas após um evento clínico grave decorrente de seu descontrole por vários anos 9 , tais como infarto agudo do miocárdio ou acidentes vasculares encefáli-cos 10,11 . Além disso, grande parte das pessoas que conhecem seu diagnóstico de HAS apresenta baixa aderência ao tratamento ou é tratada com terapêutica incorreta 10,12 .…”
unclassified
“…Estudos de base populacional foram realizados para investigar a prevalência e os fatores associados à HAS na população brasileira, no entanto expressiva parte foi direcionada a adultos, adolescentes e crianças 5,9,12,13,14 . As pesquisas com idosos restringiram-se à região sudeste do país 5,7,15 18 .…”
unclassified
“…It is worth noting the lower prevalence in the São Paulo state capital, because it was believed that the high exposure to stressors and the greater possibility of inadequate life styles and habits, characteristic of large cities, could contribute to a higher prevalence of hypertension. Brazilian studies have reported a higher prevalence of hypertension in large cities, such as the capitals of the states of Goiás (36.4%) 9 and Mato Grosso do Sul (41.4%) 10 and Brasília (37.9%) 11 , as compared with that of smaller cities, such as Sinop in the inner Mato Grosso state (23,2%) 12 , São José do Rio Preto i n the inner São Paulo state (25.2%) 13 , and Luzerna in the inner Santa Catarina state (14,7%) 14 .…”
Section: Discussionmentioning
confidence: 99%